2020
DOI: 10.1038/s41567-020-0810-3
|View full text |Cite
|
Sign up to set email alerts
|

Phase transitions in information spreading on structured populations

Abstract: Mathematical models of social contagion that incorporate networks of human interactions have become increasingly popular, however, very few approaches have tackled the challenges of including complex and realistic properties of socio-technical systems. In this work we define a framework to characterize the dynamics of the Maki-Thompson rumor spreading model in structured populations, and analytically find a previously uncharacterized dynamical phase transition that separates the local and global contagion regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(42 citation statements)
references
References 45 publications
2
39
0
1
Order By: Relevance
“…Information spreading. Efforts to simulate the spreading of information on social media by reproducing real data have mostly applied variants of standard epidemic models [37][38][39][40] . Coherently, we analyze the observed monotonic increasing trend in the way new users interact with information related to the COVID-19 by using epidemic models.…”
Section: Interaction Patternsmentioning
confidence: 99%
“…Information spreading. Efforts to simulate the spreading of information on social media by reproducing real data have mostly applied variants of standard epidemic models [37][38][39][40] . Coherently, we analyze the observed monotonic increasing trend in the way new users interact with information related to the COVID-19 by using epidemic models.…”
Section: Interaction Patternsmentioning
confidence: 99%
“…In addition, models of complex recovery, in which the social influence mechanism acts on the recovery rule rather than on the infection one, showed that this change of perspective might lead to explosive adoption dynamics [58]. This behavior is especially pronounced in spatial systems, whose effects on the contagion dynamics have also been the focus of several studies [59][60][61][62]. Yet, among humans, communication interactions can occur in groups of three or more agents, and often cannot be simply factored into a collection of dyadic contacts.…”
Section: Modeling Social Contagionmentioning
confidence: 99%
“…Unfortunately, with the spread of COVID-19 epidemic, another massive infodemic spread virally over the world with recurring drama. Previous evidence suggests that the Internet, by its very nature, could amplify and relay such infodemic swiftly worldwide, cause exaggerated panic and worsen stigmatization against people in the epicenter of outbreak progressively [16][17][18] . Much worse in the current infodemic, Corona beer is being slashed by the name's similarity to the deadly coronavirus.…”
Section: Does a Virus' Name Really Matter?mentioning
confidence: 99%